Cochlear Implant Awareness: Development and Validation of a Patient Reported Outcome Measure - Markodimitraki, Laura M.; Stegeman, Inge; Thomeer, Hans G. X. M. (Frontiers in Neuroscience, 2022)
Background: Surgical success of cochlear implantation is usually measured through speech perception and quality of life questionnaires. Although these questionnaires cover a broad spectrum of domains, they do not evaluate the consciousness of wearing a cochlear implant (CI) and how this impacts the daily life of patients. To evaluate this concept we aimed to develop and validate a standardized patient reported outcome measure (PROM) for use in cochlear implant users. Methods: Development and evaluation of the COchlear iMPlant AwareneSS (COMPASS) questionnaire was realized following the COSMIN guidelines in three phases: (1) item generation, (2) qualitative pilot study to ensure relevance, comprehensiveness, comprehensibility and face validity, and (3) quantitative survey study for the assessment of reliability (test-retest) with 54 participants. Results: Nine domains of CI awareness were identified through literature research and interviews with experts and patients. These resulted in the formulation of 18 items which were tested with a pilot study, after which 3 items were deleted. The final 15-item COMPASS questionnaire proved to have good validity and satisfactory reliability. The intraclass correlation coefficient calculated for items with continuous variables ranged from 0.66 to 0.89 with seven out of eight items scoring above the acceptable level of 0.7. The Cohen’s kappa calculated for items with nominal variables ranged from -0.4 to 0.78 with 11 (sub)items out of 15 scoring above fair to good agreement. Measurement error analysis for items with continuous variables showed a mean difference of -2.18 to 0.22. The calculated 95% limits of agreement for these items revealed no statistically significant difference between the two administered questionnaires. For items with nominal variables, the percentages of agreement calculated, ranged between 0% and 95%, and 83.3% and 96.6% for positive and negative agreement, respectively. Conclusion: The COMPASS questionnaire is a valid and reliable PROM for evaluating the cochlear implant awareness, and it can be easily used in routine clinical practice.